Mathematical model of adsorption of high molecular weight compounds in a column-type apparatus - Sabadash, Vira; Nowik-Zając, Anna; Konovalov, Oleh (Видавництво Львівської політехніки, 2024)
d substances and the design features of the equipment. The purpose of the study was to create a mathematical model that describes the process of adsorption of high-molecular compounds in a column-type apparatus, taking into account the specific properties of the adsorbed substances and the design features of the equipment. Equations that consider the kinetic aspects of adsorption and desorption are used to describe the dynamics of the process. It was noted that the large size of molecules, their complex structure, and environmental conditions can significantly affect the efficiency of the adsorption process. The model considers phenomena such as diffusion in a porous medium, the influence of competition between different components of the mixture, and possible changes in the structure of adsorbed molecules. The obtained data made it possible to determine the optimal conditions for achieving maximum adsorption efficiency and assess the effect of changing the process parameters on the initial products. Comparison of experimental and theoretical data indicates the adequacy of the obtained model and high convergence of results. The developed model can be used for forecasting and optimizing industrial processes, where the adsorption of highmolecular compounds is a crucial stage, Including biotech manufacturing, the pharmaceutical industry, water treatment, and other industries. Thanks to the possibility of predicting the system’s behaviour when conditions change, the model can be a tool for improving existing technological processes, reducing costs and improving the quality of the final product. The developed mathematical model is essential to a deeper understanding of the adsorption processes of high-molecular compounds in column-type devices. It not only allows for the analysis of the current state of the system but also provides for the possibility of its adaptation to new production conditions and needs. This opens up new opportunities for the development of technologies in various industries.
Keywords: wastewater; macromolecular compounds; adsorption dynamics; albumin; activated carbon; column-type devices